Analisis Karakteristik Keberadaan Perbankan di Nusa Tenggara Barat Terhadap Kondisi Perekonomian Daerah Menggunakan K-Means Clustering - Anisa Nurizki; Muhammad Irfan Hanifiandi Kurnia; Anwar Fitrianto; Bagus Sartono; Sachnaz Desta Oktarina; Dian Handayani (Jurnal Statistika dan Aplikasinya, 2022)
In certain areas, there are still many people who have to travel long distances to access some banks. Difficult mobility is considered to hinder business activities. The West Nusa Tenggara (NTB) Province is one of the favorite travel destinations for some foreigner tourists as well as domestic tourists because of its natural beauty and cultural diversity. the existence of some banks in the NTB Province , is important to facilitate the circulation of money. For this reason, this study aims to analyze the existence of some banks in the NTB Province and the condition of mobility in accessing themto regional economic conditions by applying K-Means clustering. Our results show that there are two clusters, , where the cluster 2 is an urban area and a tourist area. It has charactersitic has a GDP greater than cluster 1.